The Caribbean File - Richard MacAndrew (UK Cambridge University Press, 2013)
Secret agent Ian Munro is sent to the islands of the Caribbean to discover what two notorious terrorists are doing there. He tracks down the men and their beautiful female accomplice, and then follows them as they put their plan to dominate the world into action. How can he stop them? And what about the kidnapped boy and his nuclear scientist father?